Varied presentation of uterine arteriovenous malformations and their management by uterine artery embolisation. (January 2014) - Singh, N.; Tripathi, R.; Mala, Y. M.; Tyagi, S.; Tyagi, S.; Singh, C.
<x xml:space="preserve">Abstract</x> Uterine arteriovenous malformations are rare lesions which have a varied presentation that may range from the patient being asymptomatic to varying degrees of menorrhagia. It can be diagnosed by Doppler sonography but a strong index of suspicion is necessary. Management of this condition depends on presentation and available resources. In asymptomatic patients, we can leave the patients on regular follow-up as many lesions regress spontaneously. In patients with excessive haemorrhage not responding to embolisation or when facilities of embolisation are not available, hysterectomy needs to be done. Uterine artery embolisation should be considered the optimum treatment, as it has a high success rate coupled with few complications and also has fertility-preserving potential. Clinical follow-up usually suffices but sonography may occasionally be required.